The Construction of History and Political Debates on Television in the Context of Popular Television Series - İlaslan, Süleyman (İmge Kitabevi Yayınları, 2016)
Television broadcasting plays a role in shaping our relationship with history that is as fundamental as our contemporary experiences. Thus, television assumes a central position within the framework of people’s participation in historical process and understanding of history. This growing relationship between television and history results in increased political significance of history on television. This political significance is clearly evident in efforts to define the limits of television content and keep this content under control. Controversies as regards the way history is presented on television are directly related to the fact that historiography and the way history is constructed constitute a part of the political struggle. In addition to this, history becomes a more profitable commodity for television industry and history on television is considered important in the context of market priorities. As a result, debates around history and historiography on television emerges within the context of more general political and economic interests that also impact broadcasting in general. Therefore, it is believed that the relationship between television and history should be examined with a critical approach taking into account the dominant power relations in the field of broadcasting. In this sense, this study examines the political debates that have emerged in recent years around historical television series in Turkey. In this scope, this study first discusses the relationship between television and history; and then questions the reasons of debate around history on television. Secondly, the political debates around domestic historical television series which appeared between 2011-2015 are examined in the context of political use of history in Turkey. The discussions mainly focus on Muhteşem Yüzyıl, an historical television series broadcast on Star TV, but it is not only limited to this series. Thus, the study includes other domestic historical television series that were broadcast during the same period and provoked similar discussions. The focus of the study is to examine the reasons as to why politicians are involved in the discussion of the presentation of history on television with a particular focus on the relationship between the television industry and history.

Televizyon yayıncılığı çağdaş deneyimlerimiz kadar tarihle kurduğumuz ilişkilerin biçimlendirilmesinde de temel bir rol oynamaktadır. Böylece televizyon, insanların tarihsel sürece katılmaları ve tarihi anlamlandırmalarında giderek merkezi bir konuma yerleşmektedir. Televizyon ve tarih arasında artan ilişki televizyondaki tarihe verilen politik önemi beraberinde getirmektedir. Bu politik önem televizyondaki içeriklerin sınırlarını belirleme ve onları kontrol altında tutma çabalarında belirgin bir biçimde ortaya çıkmaktadır. Televizyondaki tarihin tartışmalı bir konuya dönüşmesi daha genelde tarihyazımının ve tarihin nasıl kurgulanacağının politik bir mücadele konusu olmasıyla bağlantılıdır. Ayrıca televizyon endüstrisi açısından tarihin her geçen gün giderek önemsenen bir metaya dönüştüğü görülmekte ve televizyondaki tarih piyasa öncelikleri bağlamında daha fazla önemsenmektedir. Dolayısıyla televizyondaki tarih ve tarihyazımı etrafındaki tartışmalar yayıncılığı kuşatan daha genel politik ve ekonomik çıkarlar bağlamında karşımıza çıkmaktadır. Bu çerçevede, televizyon ve tarih ilişkisinin alandaki hâkim güç ilişkilerini dikkate alan eleştirel bir yaklaşımla ele alınması gerektiği düşünülmektedir. Çalışmada son yıllarda Türkiye’de tarihi konu edinen televizyon dizileri etrafında yükselen tartışmalar ele alınmaktadır. Öncelikle televizyon ve tarih ilişkisi tartışılmakta ve tarihin politik kullanımı bağlamında televizyondaki tarihin tartışma konusu olma nedenleri sorgulanmaktadır. Ardından Türkiye’de tarihin yoğun bir biçimde kullanılan politik malzemeye dönüşmesi çerçevesinde tarihi konu edinen yerli televizyon dizileri etrafında 2011-2015 yılları arasında yükselen politik tartışmalar incelenmektedir. Tartışmalar Star TV’de yayınlanmış olan Muhteşem Yüzyıl dizisi etrafında yoğunlaşmaktadır, ancak bu diziyle sınırlı kalmamaktadır. Dolayısıyla inceleme bu diziyle aynı dönemde yayınlanmış olan ve bağlantılı olarak tartışılan diğer yerli tarih dizilerini de ele almaktadır. Çalışmanın odak noktası Türkiye’de politikacıların televizyondaki tarihi tartışma konusu etme nedenlerini televizyon endüstrisi ve tarih arasındaki ilişki bağlamında sorgulamaktır.
Popüler Tarih Dizileri Bağlamında Televizyonda Tarih İnşası ve Politik Tartışmalar
Keywords: Radio-Television; Radyo-Televizyon